Python passive network mapping : P2NMAP - Hosmer, Chet (Syngress Publishers, is an imprint of Elsevier, 2015)
This book reveals a revolutionary and open source method for exposing nefarious network activity. Hosmer shows how to effectively and definitively passively map networks. Active or probing methods to network mapping have traditionally been used, but they have many drawbacks - they can disrupt operations, crash systems, and - most importantly - miss critical nefarious activity. It provides new innovations to passive network mapping, while delivering open source Python-based tools that can be put into practice immediately. --